Studying the genotype of Aryl Hydrocarbon Receptor-Interacting Protein (AIP) Gene (rs641081C>A) in ‎Iraqi Samples with Acromegaly Pituitary Adenoma (Baghdad Science Journal, 2022)
Pituitary adenomas are the anterior pituitary tumors. Patients with an Aryl Hydrocarbon Receptor-Interacting Protein (AIP) mutation (AIP- mut) tend to have more aggressive tumors occurring at a younger age. Single nucleotide polymorphisms (SNPs) in many studies have been related to metabolic comorbidities in the general population. Study aims investigated the role of AIP gene SNPs with susceptibility to acromegaly pituitary- adenoma, with levels of LH, FSH, TSH, Testosterone, IGF1,GH, FT4 , Prolactin hormones and blood sugar levels. The study ‎was conducted on a group of acromegaly patients, including 50 patients) both Genders( with ‎hyperplasia of the ends, and apparently healthy control group. Genotyping of AIP gene SNP (rs641081C >A‎) was indicated significant differences in frequency percentage between the study groups. The frequency of heterozygous CA genotype was significantly (p<0.01) higher in the patients' group when compared with control. The Means of IGF1, GH, prolactin, testosterone, and FBS were significantly ‎higher in patients at first treatment than that in control.‎ While,‎ the means of IGF1, GH, prolactin, and testosterone increased significantly in patients at last treatment than control. Patients mean level of TSH decreased significantly at last ‎treatment. No significant differences (P ≥ 0.05) were detected between study ‎groups in all other values.‎ The Means of IGF1, GH, and prolactin at first and last treatment were significantly decreased, while LH ‎was significantly increased at last treatment. In ‎patients with heterozygous mutant and wild genotype, means of IGF1, GH, and ‎prolactin decreased significantly at last treatment compared ‎to first treatment. ‎In this study heterozygous rs641081C>A showed a risk factor for susceptibility of acromegaly. Also, serum IGF1, GH, prolactin, were affected by the SNP of AIP gene within carriers of genotypes of rs641081C>A. IGF1, prolactin and GH ‎decreased significantly at last treatment compared to first treatment.